Quality of life in total knee replacement (TKR) patients – A review - M. Ranga Priya; M. Karthika; Meril Lucy Shibu; B. Kowsalya; Lini Jacob (Creative Pharma Assent, 2020)
Worldwide, severe pain and disability are caused to patients by Osteoarthritis, which is a common condition of the joints. A need for knee replacement had become a great option for patients when conventional treatment fails in granting appropriate relief in them, especially in elderly patients. Like all joint replacement surgeries, a total knee replacement procedure is also a quite painful and risky procedure that requires sufficient postoperative rehabilitation and therapies to prevent further complications. Post-surgical pain had a great influence on the patients' quality of life and a need to measure pain intensity had become a basic requirement. Measuring pain intensity can be done using traditional pain scales like a visual analogue scale (VAS), and a numerical rating scale (NRS). A risk assessment and predictor tool (RAPT) determines the discharge accuracy in patients. The WOMAC scale which is the abbreviated form of the questionnaire for checking the health status of the patients known as the Western Ontario and McMaster University Osteoarthritis Index. This questionnaire is used to assess the quality of life of the osteoarthritis patients after a surgery for the total knee replacement. The results of the assessment show that pain had become a significant factor in the reduction in quality of life. In conclusion, a well-designed multimodal analgesic regimen should be incorporated into the patient's rehabilitation care, which in turn will intensify the patient's quality of life, lessen the hospital stay, and minimize the socio-economic burden